2013
DOI: 10.1373/clinchem.2012.198614
|View full text |Cite
|
Sign up to set email alerts
|

Defining High-Sensitivity Cardiac Troponin Concentrations in the Community

Abstract: BACKGROUND: High-sensitivity cardiac troponin (hscTn) assays are now available that can detect measurable troponin in significantly more individuals in the general population than conventional assays. The clinical use of these hs-cTn assays depends on the development of proper reference values. Therefore, our objective was to define hs-cTnI reference values and determinants in the general community, in a healthy reference cohort, and in subsets with diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(81 citation statements)
references
References 40 publications
8
72
0
1
Order By: Relevance
“…The total number of cardiomyocytes renewed per day might strictly depend on myocardial mass that, in healthy men, is usually greater than in healthy women. Few available experimental data indicate that circulating cTn levels are strictly related to both ventricular mass and gender in large populations of healthy subjects [103][104][105][106]. A recent study on 4139 subjects (2099 M and 2040 F, age range 35-74 years) found that several variables, estimated by echocardiography and reflecting cardiovascular phenotypes (including left ventricular mass), were significantly correlated with cTnI concentrations in the general population, and that their distribution differed according to gender and age [105] (Table 3).…”
Section: Mechanisms Of Troponin Release In Cardiac Patients and Healtmentioning
confidence: 99%
“…The total number of cardiomyocytes renewed per day might strictly depend on myocardial mass that, in healthy men, is usually greater than in healthy women. Few available experimental data indicate that circulating cTn levels are strictly related to both ventricular mass and gender in large populations of healthy subjects [103][104][105][106]. A recent study on 4139 subjects (2099 M and 2040 F, age range 35-74 years) found that several variables, estimated by echocardiography and reflecting cardiovascular phenotypes (including left ventricular mass), were significantly correlated with cTnI concentrations in the general population, and that their distribution differed according to gender and age [105] (Table 3).…”
Section: Mechanisms Of Troponin Release In Cardiac Patients and Healtmentioning
confidence: 99%
“…However, the real-world pro-cess leading to the selection of "normal" subjects across different studies is highly variable, ranging from a failure to supply a detailed definition of how normal subjects were selected (10 -16 ), to primarily using health questionnaires or reviewing baseline clinical characteristics (17)(18)(19)(20)(21)(22)(23)(24), to more selective screening methods using surrogate blood biomarkers, electrocardiography, imaging, and/or physical examination in addition to assessment of known baseline clinical variables (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Several studies have relied exclusively on questionnaires to define reference individuals.…”
Section: Defining Normalitymentioning
confidence: 99%
“…Most importantly, 99th percentiles were calculated as absolute, single, upper 99th percentile values. In the second study, McKie et al (34 ), using the Siemens Dimension Vista assay, defined hscTnI reference values in both community-based and healthy reference cohorts. Participants underwent clinical assessment and echocardiographic imaging evaluation, as well as surrogate biomarker screening.…”
Section: Defining Normalitymentioning
confidence: 99%
See 2 more Smart Citations